The persistent power of human rights: From commitment to compliance - Risse, Thomas 1955-; Ropp, Steve C.; Sikkink, Kathryn 1955- (Cambridge (UK): Cambridge University Press, 2013)
"The Power of Human Rights (published in 1999) was an innovative and influential contribution to the study of international human rights. At its centre was a 'spiral model' of human rights change which described the various socialisation processes through which international norms were internalised into the domestic practices of various authoritarian states during the Cold War years. The Persistent Power of Human Rights builds on these insights, extending its reach and analysis. It updates our understanding of the various casual mechanisms and conditions which produce behavioural compliance, and expands the range of rights-violating actors examined to include democratic and authoritarian Great Powers, corporations, guerilla groups and private actors. Using a unique blend of quantitative and qualitative research and theory, this book yields not only important new academic insights but also a host of useful lessons for policymakers and practitioners"--Back cover.
Introduction and stock-taking: Introduction and overview / Thomas Risse and Stephen C. Ropp ; The power of human rights a decade after : from euphoria to contestation? / Anja Jetschke and Andrea Liese ; From ratification to compliance : quantitative evidence on the spiral model / Beth A. Simmons -- Conceptual and methodological issues: Human rights in areas of limited statehood: the new agenda / t From commitment to compliance : companies, rebels, individuals: Encouraging greater compliance : local networks and the United Nations global compact / Wagaki Mwangi, Lothar Rieth and Hans Peter Schmitz ; Business and human rights : how corporate norm violators become norm entrepreneurs / Nicole Deitelhoff and Klaus Dieter Wolf ; Taming of the warlords : commitment and compliance by armed opposition groups in civil wars / Hyeran Jo and Katherine Bryant ; Changing hearts and minds : sexual politics and human rights / Alison Brysk ; Conclusions / Thomas Risse and Kathryn Sikkink.
Includes bibliographical references (pages 296-333) and index.
Keywords: Human rights; Human Rights; Droits de l'homme (Droit international); POLITICAL SCIENCE -- International Relations -- General; Droits de l'homme.; Politics and Government; Human rights; Menschenrecht; Rechtsgeltung; Human rights; Politics and Government